Semantic processing of concrete and abstract concepts in semantic variant- Primary Progressive Aphasia - Martínez-Cuitiño, Macarena; Soriano, Federico; Formoso, Jesica; Borovinsky, Geraldine; Ferrari, Jesica; Pontello, Noelia; Barreyro, Juan Pablo; Manes, Facundo (Revista de Investigación en Logopedia, 2018)
Semantic variant Primary Progressive Aphasia (sv-APP) is characterized by progressive affectation of conceptual knowledge. Previous investigations have reported a higher affectation for abstract concepts than for concrete ones. This is known as a concreteness effect. Nonetheless, there are works that have spotted an inverse concreteness effect, that is, subjects better performance with abstract concepts. In this investigation we compared the performance of 8 sv-APP patients to a group of 20 healthy controls matched in age and education level, using a synonyms task. Results show a concreteness effect, this means, a better performance with concretes concepts for nouns and verbs. These findings agree with previous research that found a worse performance with abstract concepts in sv-APP patients. These findings support the idea of an amodal semantic hub which processes both types of concepts. The observed low affectation in concrete concepts could be explained by higher semantic richness.
Keywords: concrete concepts; abstract concepts; semantic variant primary progressive aphasia; concreteness effect; grammatical category